Validation of the Social and Emotional Competencies Questionnaire for 4th to 6th graders - Vítor Alexandre Coelho; Vanda Sousa (INFAD, 2020)
In the last two decades, Social and Emotional Learning had become a global phenomenon. However, the growth that took place in program creation has not been matched by an equivalent growth in the development of evalutation instruments. The lack of proper assessment tools creates several problems for the evaluation of programs’ effectiveness. The present study displays the validation of an instrument (already validated for older students), to a younger student population (nine to 12-year olds); the Social and Emotional Competencies Evaluation Questionnaire (Coelho, Marchante, Sousa, 2014). Seven-hundred-sixty-five 4th to 6th grade students (52.7% boys) filled out the instrument; students’ age ranged nine to 12 years (Midade = 10.07; SD = 1.26). A Confirmatory Factor Analysis was conducted, as well as internal consistency and concurrent validity analyses. Gender and age effects were also analyzed. Results indicate that this version of the QACSE is composed by 39 items and has a bifactorial structure, composed by four correlated social and emotional competencies; self-control, social awareness, relationship skills and responsible decision making. The QACSE also includes two dimensions of social and emotional difficulties; social isolation and social anxiety. All the dimensions of the current version of the questionnaire displayed very high levels of correlation with their respective counterpart in a similar questionnaire. Gender differences were also found, girls reported higher levels of self-control, social awareness, responsible decision making and social anxiety. Therefore, it is possible to conclude that QACSE was shown to be a quick, valid and reliable instrument to assess the multiple dimensions of social and emotional competencies of nine to 12-year old students.